On The Fabrication of Cultural Memory: History Theme Malls in Dubai - Biln, John (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2016)
Dubai, one of the most mobile cities in the world, is rapidly cementing its image as a global city and icon of Islamic tolerance. Dubaiâ€™s economic opportunities, relative safety and geographic centrality in the heart of the Middle East make it attractive to a wide range of economic and political migrants from across the region. This article asks how a city which is overwhelmingly populated by members of a highly mobile and diverse non-citizen workforce could construct a plausible sense of collective memory, a fundamental requirement for any meaningful social cohesion. In considering this question, the article reviews two well-known history-themed commercial centers, Ibn Batutta Mall and the Khan Murjan in Wafi Mall. Each of these emphasize Arab-Islamic cultural heritage and the regionâ€™s long history of trade and transit. Both malls highlight culturally significant journeys documented in historical manuscripts. The article concludes that in constructing a complex experience which maps immediate spatial movement onto well-known travel narratives, the Ibn Battuta and Khan Murjan centers provide scaffolds for a cultural memory essentially â€œmade to orderâ€ for a population who share, if little else, a profound sense of dislocation, flow and perpetual movement.